Pengaruh Kualitas Pelayanan Dan Fasilitas Kesehatan Terhadap Tingkat Kepuasan Pasien Di Puskesmas Pegadungan 1: The Influence of the Quality of Health Services and Facilities on Patient Satisfaction Level at Pegadungan Health Center 1 - Guntur Setiawan Putra; Usran Masahere (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to analyze the effect of service quality and health facilities on patient satisfaction at Pegadungan 1 Community Health Center. The population of this study consisted of all patients at Pegadungan 1 Community Health Center during the research period, with a sample of 54 respondents. Data were collected through observation, questionnaire distribution, and literature review. The data analysis techniques included data quality testing, reliability testing, classical assumption testing, and multiple linear regression analysis using SPSS software. The results indicate that all research instruments were valid and reliable. Classical assumption testing shows that the data were normally distributed and free from multicollinearity, thus meeting the assumptions of regression analysis. The multiple linear regression analysis shows that service quality and health facilities have a positive and significant effect on patient satisfaction, both partially and simultaneously (p < 0.05). The Adjusted R Square value of 0.794 indicates that service quality and health facilities explain 79.4% of the variation in patient satisfaction, while the remaining 20.6% is influenced by other variables outside this study.